Peran Multiaktor dalam Implementasi Kebijakan Penanggulangan Bencana Erupsi Gunung Lewotobi: Studi Kecamatan Wulanggitang, Kabupaten Flores Timur, Nusa Tenggara Timur - Petrus Arselius Mari Sogen; Petrus Kase; Ardy Yosafat Pandie (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
The eruption of Mount Lewotobi has significantly affected communities in Wulanggitang District, requiring the involvement of multiple actors in disaster management. This study aims to analyze multi-actor roles in implementing disaster management policy through the dimensions of expectation, norm, and performance. A descriptive qualitative approach with a case study design was employed. Data were collected through observation, in-depth interviews with 17 purposively selected informants, and document analysis. The data were examined using the interactive model of Miles, Huberman, and Saldaña, while validity was established through source, technique, and time triangulation. The findings show that the local government, BPBD, Social Service, village governments, NGOs, volunteers, media, private sector, and communities performed roles broadly consistent with their functions. Their collaboration supported evacuation, evacuee registration, logistics distribution, emergency education, and psychosocial services. Nevertheless, role gaps remained in early information delivery, evacuation transport, equitable aid distribution, permanent housing, and interagency data integration. Limited personnel, funding, community preparedness, and sociocultural considerations also constrained implementation. The policy was therefore moderately effective but requires stronger early-warning systems, integrated data, institutional capacity, and sustainable socioeconomic recovery.